Characterization and genetic diversity of brinjal germplasm - Islam, MT; Chhanda, RA; Pervin, N; Hossain, MA; Chowdhury, RU (Bangladesh Journal of Agricultural Research, 2018)
The experiment was carried out in a non replicated design with 40 accessions of brinjal (Solanum melongena L.) at Plant Genetic Resources Centre (PGRC), BARI Gazipur to characterize and study the genetic diversity and identify the useful traits. Each accession of nine plants was grownin a 3 X 2 m size plot. The accessions were collected from 16 districts of Bangladesh. Two to four classes were found for plant growth habit, leaf blade lobing, leaf prickles, flower colour, fruit shape, fruit apex shape and fruit colour distribution. The accessions exhibited 64% straight, 13% both slightly curved and curved, and 10% snaked shaped edible fruit along with 55% purple and 45% green fruit. Fruit length of accessions ranged from 5 to 31.23 cm, breadth 2.4 to 10.6 cm, weight 13 to 95.2 g and 3 to 30 fruits per plant. The accessions were grouped into five clusters. The inter and intra cluster distances ranged from 4.01 to 8.32 and 0.94 to 1.36, respectively. Accessions collected from the same districts felt into different clusters. The results obtained by D2 analysis were also confirmed by canonical analysis. Crosses BD-7327 (Rangpur) of cluster II with BD-9954 (Chittagong) of Cluster-III and BD-7319 (Panchagarh) of Cluster-I with BD-11732 (Bandarban) of cluster V, could be performed for obtaining wider variability in the segregating generations. The breeders could use the selected accessions for varietal improvement of brinjal. Bangladesh J. Agril. Res. 43(3): 499-512, September 2018